Accumulation measurements from stake farm Neumayer Pegelfeld Süd, Ekström Ice Shelf, Antarctica, 1991-2024 (interpolated to monthly resolution) - Reppert, Valerie; Eisen, Olaf (PANGAEA, 2025)
This publication series contains the accumulation measurements from stake farm Pegelfeld Süd on the Ekström Ice Shelf, Antarctica. The stake farm, located approximately 6 km to the southwest from the past and present Neumayer Station, has been in operation since December 1990. It consists of 16 aluminum poles (balise), placed in a grid of 4 x 4. Readings have been carried out in bi-weekly to monthly intervals by the overwintering staff of the air chemistry observatory (Spuso). This time series is interpolated to monthly resolution to remove the influence of irregular measurements in time. The original data on the irregular time grid will also be provided in the bibliography https://doi.pangaea.de/10.1594/PANGAEA.971649. The time series contains the monthly mean accumulation rates (in cm/day), weighted by the number of days, for which the accumulation rate of the irregular measurements has been valid. Additionally, the accumulation rate per month is provided, by multiplying the monthly mean accumulation rate per day with the number of days in the corresponding month. The cumulative accumulation is the cumulative sum of the accumulation rate per month.
Keywords: Antarctica; Neumayer Station; snow accumulation